2019
DOI: 10.1016/j.tra.2018.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Where does active travel fit within local community narratives of mobility space and place?

Abstract: Encouraging sustainable mobility patterns is at the forefront of policymaking at all scales of governance as the collective consciousness surrounding climate change continues to expand. Not every community, however, possesses the necessary economic or socio-cultural capital to encourage modal shifts away from private motorized vehicles towards active modes. The current literature on 'soft' policy emphasizes the importance of tailoring behavior change campaigns to individual or geographic context. Yet, there is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Some of this work has suggested that investments in infrastructure such as bike lanes and bicycle sharing stations, in isolation, are insufficient to encourage notable shifts to cycling, particularly when these investments are made in the otherwise unsuitable or unsupportive environments that tend to be disproportionately faced in low-income communities of color (Dill et al 2014; Wang and Lindsey 2019). Other research has focused on the role of perceptions and attitudes, finding these and other forms of social support to be important determinants of cycling—particularly among low-income populations and people of color—that warrant consideration alongside infrastructure investments (Barajas 2019; Biehl et al 2019; Dill et al 2014). Pritchard et al (2019) note that some structural barriers to cycling, such as the socio-spatial distribution of employment opportunities and corresponding commute distances, may be challenging to overcome.…”
Section: Discussionmentioning
confidence: 99%
“…Some of this work has suggested that investments in infrastructure such as bike lanes and bicycle sharing stations, in isolation, are insufficient to encourage notable shifts to cycling, particularly when these investments are made in the otherwise unsuitable or unsupportive environments that tend to be disproportionately faced in low-income communities of color (Dill et al 2014; Wang and Lindsey 2019). Other research has focused on the role of perceptions and attitudes, finding these and other forms of social support to be important determinants of cycling—particularly among low-income populations and people of color—that warrant consideration alongside infrastructure investments (Barajas 2019; Biehl et al 2019; Dill et al 2014). Pritchard et al (2019) note that some structural barriers to cycling, such as the socio-spatial distribution of employment opportunities and corresponding commute distances, may be challenging to overcome.…”
Section: Discussionmentioning
confidence: 99%
“…As in other neighbourhoods, connectivity with the wider network is also likely to be important in increasing the perceived viability of cycling. Indeed, as has been noted in other low-income, ethnically diverse communities internationally (Biehl et al, 2019), participants in this study discussed the need to access places beyond their own neighbourhood due to its perceived lack of amenities.…”
Section: Discussionmentioning
confidence: 75%
“…Over the last decade, equity-oriented studies have highlighted social-spatial inequalities encompassing active mobility in cities worldwide ( Biehl et al, 2019 ; Feitelson, 2002 ; Lee et al, 2017 ). Empirical evidence indicates that despite the general political efforts to improve cycling conditions in cities, the use of the bicycle for daily activities remains limited to specific demographic and socioeconomic segments of society ( Goodman et al, 2013 ; Mora et al, 2021 ; Tucker & Manaugh, 2018 ).…”
Section: Gender Differences In Cyclingmentioning
confidence: 99%